2011
DOI: 10.1002/jpln.201000134
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term‐fertilization effects on soil organic carbon, physical properties, and wheat yield of a loess soil

Abstract: The large dryland area of the Loess Plateau (China) is subject of developing strategies for a sustainable crop production, e.g., by modifications of nutrient management affecting soil quality and crop productivity. A 19 y long‐term experiment was employed to evaluate the effects of fertilization regimes on soil organic C (SOC) dynamics, soil physical properties, and wheat yield. The SOC content in the top 20 cm soil layer remained unchanged over time under the unfertilized plot (CK), whereas it significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 29 publications
6
64
2
Order By: Relevance
“…The application of different long-term fertilization regimes could lead to a great change of soil characteristics, such as levels of organic C, P, and the pH (Dong et al 2012;Ge et al 2008;Liu et al 2013;Yang et al 2011;Zheng et al 2008a, b), which could affect the fraction and bioavailability of metal in soil, thereby posing risk to agricultural products. Sequential chemical extraction does not represent the actual bioavailability of As in soil.…”
Section: Application Of Biosensor To Assess the Bioavailable As In DImentioning
confidence: 99%
See 3 more Smart Citations
“…The application of different long-term fertilization regimes could lead to a great change of soil characteristics, such as levels of organic C, P, and the pH (Dong et al 2012;Ge et al 2008;Liu et al 2013;Yang et al 2011;Zheng et al 2008a, b), which could affect the fraction and bioavailability of metal in soil, thereby posing risk to agricultural products. Sequential chemical extraction does not represent the actual bioavailability of As in soil.…”
Section: Application Of Biosensor To Assess the Bioavailable As In DImentioning
confidence: 99%
“…It has been reported that the application of inorganic or organic fertilizers can increase the content of organic carbon in soil and maintain soil productivity (Liu et al 2013;Yang et al 2011). Additionally, it has been confirmed that As mobilization is associated with the concentration of dissolved organic carbon ND not determined in soil, which is due to the organic ligands of dissolved organic carbon (DOC) that facilitate the release of inactive As (F4 fraction) to active soluble As (F1 fraction) through competitive sorption or through solution complexation (Cao et al 2003;Harvey et al 2002;Jackson et al 2006;Mladenov et al 2010).…”
Section: Factors Governing the Difference Of Bioavailable Asmentioning
confidence: 99%
See 2 more Smart Citations
“…7], indicating that agricultural soils may have a potential to mitigate climate change through C sequestration [8,9]. Besides climate change, SOC has a number of potential associated benefits, including: increased soil fertility [10,11]; improved biological and physical soil characteristics [12] via a reduction in bulk density, improved waterholding capacity and enhanced activity of soil microbes [13] (although this may increase CO 2 emission). Promoting SOC also often increases soil biodiversity and ecosystem functions that can enhance agricultural productivity by mediating nutrient cycling, soil structure formation, and crop resistance to pests and diseases [14].…”
Section: Introductionmentioning
confidence: 99%